Inhibitory potential of omega-3 fatty and fenugreek essential oil on key enzymes of carbohydrate-digestion and hypertension in diabetes rats - Hamden Khaled (Lipids in Health and Disease, 2011)
Abstract Background diabetes is a serious health problem and a source of risk for numerous severe complications such as obesity and hypertension. Treatment of diabetes and its related diseases can be achieved by inhibiting key digestives enzymes-related to starch digestion secreted by pancreas. Methods The formulation omega-3 with fenugreek terpenenes was administrated to surviving diabetic rats. The inhibitory effects of this oil on rat pancreas α-amylase and maltase and plasma angiotensin-converting enzyme (ACE) were determined. Results the findings revealed that administration of formulation omega-3 with fenugreek terpenenes (Om3/terp) considerably inhibited key enzymes-related to diabetes such as α-amylase activity by 46 and 52% and maltase activity by 37 and 35% respectively in pancreas and plasma. Moreover, the findings revealed that this supplement helped protect the β-Cells of the rats from death and damage. Interestingly, the formulation Om3/terp modulated key enzyme related to hypertension such as ACE by 37% in plasma and kidney. Moreover administration of fenugreek essential oil to surviving diabetic rats improved starch and glucose oral tolerance additively. Furthermore, the Om3/terp also decreased significantly the glucose, triglyceride (TG) and total-cholesterol (TC) and LDL-cholesterol (LDL-C) rates in the plasma and liver of diabetic rats and increased the HDL-Cholesterol (HDL-Ch) level, which helped maintain the homeostasis of blood lipid. Conclusion overall, the findings of the current study indicate that this formulation Om3/terp exhibit attractive properties and can, therefore, be considered for future application in the development of anti-diabetic, anti-hypertensive and hypolipidemic foods.